2020
DOI: 10.1029/2020ja028150
|View full text |Cite
|
Sign up to set email alerts
|

20 Years of ACE Data: How Superposed Epoch Analyses Reveal Generic Features in Interplanetary CME Profiles

Abstract: Interplanetary coronal mass ejections (ICMEs) are magnetic structures propagating from the Sun's corona to the interplanetary medium. With over 20 years of observations at the L1 libration point, ACE offers hundreds of ICMEs detected at different times during several solar cycles and with different features such as the propagation speed. We investigate a revisited catalog of more than 400 ICMEs using the superposed epoch method on the mean, median, and the most probable values of the distribution of magnetic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 89 publications
(138 reference statements)
10
49
0
Order By: Relevance
“…Sheath events listed by Kilpua et al (2019) for the years 1997-2018 with some additional events listed by Regnault et al (2020) have been analyzed in this study. OMNI data were used to identify sheaths in the list given by Kilpua et al (2019); a few sheaths with Wind data gaps were excluded, leaving a total of 79 sheaths analyzed in the present study (Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Sheath events listed by Kilpua et al (2019) for the years 1997-2018 with some additional events listed by Regnault et al (2020) have been analyzed in this study. OMNI data were used to identify sheaths in the list given by Kilpua et al (2019); a few sheaths with Wind data gaps were excluded, leaving a total of 79 sheaths analyzed in the present study (Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…The properties of interplanetary CMEs (or ICMEs; e.g., Kilpua et al, 2017) have been studied mainly around 1 AU (e.g., Cane & Richardson, 2003;Jian et al, 2006Jian et al, , 2018Nieves-Chinchilla et al, 2019;Owens, 2018;Regnault et al, 2020;I. G. Richardson & Cane, 2010), that is where continuous in-situ measurements of the solar wind have been available for several decades and up to this day.…”
mentioning
confidence: 99%
“…The superposed epoch analysis (or Chree analysis, Chree 1913) consists in normalizing a dataset, com-monly a time series of different events on a similar timescale, and obtaining the time series' behavior of a statistically relevant parameter for each normalized time bins. In the context of ICMEs, previous studies (Lepping et al 2003;Rodriguez et al 2016;Masías-Meza et al 2016;Janvier et al 2019;Regnault et al 2020) typically take well-defined times for the normalization: the time of the discontinuity, the start time of the ME or MC, and the end time of the ME or MC. In the following, the normalization is similar to the studies of Masías-Meza et al (2016); Regnault et al (2020): the unit time for the normalized time series is taken as the length of the sheath (if it exists), and the ME is normalized to three times this unit time.…”
Section: The Superposed Epoch Era Methods Applied To Gcrsmentioning
confidence: 99%
“…In the context of ICMEs, previous studies (Lepping et al 2003;Rodriguez et al 2016;Masías-Meza et al 2016;Janvier et al 2019;Regnault et al 2020) typically take well-defined times for the normalization: the time of the discontinuity, the start time of the ME or MC, and the end time of the ME or MC. In the following, the normalization is similar to the studies of Masías-Meza et al (2016); Regnault et al (2020): the unit time for the normalized time series is taken as the length of the sheath (if it exists), and the ME is normalized to three times this unit time. This choice is motivated by the previously cited studies, which observed that sheaths have on average a duration three times less that of the ME.…”
Section: The Superposed Epoch Era Methods Applied To Gcrsmentioning
confidence: 99%
See 1 more Smart Citation